An unkindness of magicians - Howard, Kat (Saga Press, an imprint of Simon & Schuster, Inc., 2017)
There is a dark secret that is hiding at the heart of New York City and diminishing the city's magicians' power in this fantasy thriller by acclaimed author Kat Howard. In New York City, magic controls everything. But the power of magic is fading. No one knows what is happening, except for Sydney--a new, rare magician with incredible power that has been unmatched in decades, and she may be the only person who is able to stop the darkness that is weakening the magic. But Sydney doesn't want to help the system, she wants to destroy it. Sydney comes from the House of Shadows, which controls the magic with the help of sacrifices from magicians--